Aerobic biological treatment of wastewaters containing dichloromethane - Moura, Sandra C. (2011)
BACKGROUND: Volatilization has been advanced as one of the predominant phenomena contributing to volatile organic carbon emissions from wastewater treatment plants (WWTPs). In this study, strategies for minimizing such air stripping losses when treating a liquid stream containing dichloromethane (DCM), aiming at decreasing the overall emission inventory from WWTPs, were investigated. RESULTS: System R1, consisting of a continuous flow stirred tank reactor (CSTR) treating a liquid stream containing DCM at a concentration of 12 mmol dm−3 presented a biodegradation efficiency (BE) of 68%, based upon chloride release, with 10% of measurable losses, mainly due to volatilization, and 22% of unmeasurable losses. System R2 introduced operational designs aiming at decreasing DCM volatilization. In Experiment R2.1, a biotrickling filter, through which the air stripped from the CSTR was driven, was introduced leading to a reduction from 10% to 7% on the measurable losses. In Experiment R2.2, the air stripped from the CSTR was recirculated at a flow rate of 2.4 dm3 h−1 through the reactormedium before entering the biotrickling filter. The BE was improved from 69% to 82% and the losses associated with air stripping were successfully reduced to 2%. The proposed design, including air recirculation and the biotrickling filter, increased the ratio between the biodegradation rate and the volatilization rate from 7 to 41. CONCLUSIONS: Recirculation of the gaseous effluent through the reactor medium, which allowed for higher residence time within the bioreactor, was shown to be a successful strategy for improving the treatment process, thus minimizing DCM volatilization losses.